Clinical and radiological findings of incidental Rathke's cleft cysts in children and adolescents - Yeon Joung Oh; Hong Kyu Park; Seung Yang; Jun Ho Song; Il Tae Hwang (Korean Society of Pediatric Endocrinology, 2014)
PurposeIn the pediatric population, Rathke's cleft cysts (RCCs) are known to be an infrequent cause of headaches, visual disturbances, and pituitary dysfunction. We investigated the clinical characteristics of children in whom RCCs were incidentally discovered and evaluated whether RCCs influence the treatment response of patients with proven endocrinopathy.MethodsA retrospective analysis was conducted in 34 patients with RCCs who were diagnosed between 2006 and 2013 at Hallym University Medical Center. Their clinical, hormonal, and imaging findings were reviewed. We evaluated the clinical outcomes of the patients with concomitant RCCs and endocrinopathy compared to matched controls.ResultsTwenty-six of 34 patients with radiologically proven RCCs had endocrine disorders. They were 9 boys and 17 girls, with ages ranging from 4.8 to 17.4 years at the time of the diagnosis. Of these, 7 (27%) had idiopathic short stature, 7 (27%) had growth hormone deficiency (GHD), and 12 (46%) had central precocious puberty (CPP). Nineteen of 26 patients (73.1%) showed low signal intensities on T1-weighted images (T1WI) and high signal intensities on T2-weighted images. The incidence of hypointensity on T1WI was higher in the patients with RCCs accompanied by endocrinopathy than in those without endocrinopathy (P=0.033). The treatment outcomes of the patients with CPP and GHD with and without RCCs were similar.ConclusionCPP and GHD patients with a small RCC (less than 20 mm) expressing cystic magnetic resonance intensity can be managed with medical treatment, although the RCCs need to be closely monitored in radiological studies to observe their growth.